Oxygen transfer and gas holdup in airlift bioreactors assembled with helical flow promoters - Picão, Bruno W. [UNESP] (2023)
Bioreactors can perform biochemical conversions mediated by biocatalysts, such as enzymes, animal cells, plants, and microorganisms. Among several existing models, airlift bioreactors are devices with the low shear environment and good mass transfer with low energy consumption, employed in several biochemical processes. The fluid flow is enabled through air injection by the sparger located at the bioreactor base. Despite its simple geometry compared with the conventional bioreactors, airlift performance can be optimized via geometrical modifications. Therefore, the objective of this work was to evaluate the effects of the addition of helical flow promoters, positioned in the riser and/or downcomer regions of an airlift of concentric tubes measuring the volumetric oxygen coefficient (kLa) and gas holdup. The results obtained by varying the gas flow rate from 1.0 to 4.0 vvm allowed the system evaluation of oxygen transfer and gas holdup. The inclusion of helical flow promoters increased the kLa, reaching up to 23% in oxygen transfer compared to tests without helicoids and up to 14% increase in the gas holdup. The inclusion of helical flow promotors was beneficial for all gas flow rates. Thus, including these flow promoters is an effective strategy to increase the oxygen transfer rate for bioprocess optimization.